Hydrodynamic studies comparison by simulation with experimental results of reverse fluidized bed - Upender, H; Pavan Kumar, L; K. Anand Kishore, Dr (International Journal of Engineering and Technology, 2018)
In present days we are much believed computer aided (simulation) results much more than our experimental results even though time consumption, low-cost processes and we can get the efficient results when compare to experimental results. In this task, I compared my experimental results with simulation results (Ansys fluent version 17.2) in the solid liquid reverse fluidized bed system. In this, I did this comparison using Gidaspow drag model and remaining parameters were same the particle diameter was changed. I found that the hydrodynamic behavior by experimentally and by simulation those were bed height profile, pressure drop profile and Voidage profile by changing the velocity profileÂ Â